2018
DOI: 10.1253/circj.cj-18-0264
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter Aortic Valve Replacement for Severe Aortic Stenosis Complicated by Sigmoid Septum

Abstract: Background:In patients undergoing transcatheter aortic valve replacement (TAVR) for severe aortic stenosis (AS), a sigmoid septum, characterized by subaortic interventricular hypertrophy, often results in the need for new pacemaker implantation (PMI). In this study, we reviewed the feasibility and treatment efficacy of TAVR for AS in patients with a sigmoid septum. Methods and Results:Between 2011 and 2016, 48 patients (25.4%; mean age 84.9±5.4 years; 9 males) with a sigmoid septum and 141 (74.6%; mean age 82.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 22 publications
1
13
0
Order By: Relevance
“…None of the other predictors of LVOT obstruction were identified in our patient. Although sigmoid septum is not an established indication for SAVR over TAVR, TAVR has been associated with increased risk for pacemaker requirement, and if significant LVOTO can be shown pre-operatively, SAVR can potentially be combined with a myectomy ( 9 ).…”
Section: Discussionmentioning
confidence: 99%
“…None of the other predictors of LVOT obstruction were identified in our patient. Although sigmoid septum is not an established indication for SAVR over TAVR, TAVR has been associated with increased risk for pacemaker requirement, and if significant LVOTO can be shown pre-operatively, SAVR can potentially be combined with a myectomy ( 9 ).…”
Section: Discussionmentioning
confidence: 99%
“…The overall prevalence of new permanent pacemaker implantation occurred in 6844 (26.3%) of the 25,967 patients (p = .00001) (RR 115.16[95%CI 29.80-415.10]; I 2 = 69%). Figure 1 Secondary outcomes: All-cause mortality was reported in thirteen studies [10][11][12][13][14][15][16][17][18][19][20][21]23…”
Section: Primary Outcomementioning
confidence: 99%
“…A total of fourteen ( 14) studies were included in the meta-analysis. [10][11][12][13][14][15][16][17][18][19][20][21][22][23] Primary outcomes included (rate of new pacemaker implantation in patients undergoing transcatheter aortic valve replacement at 1 year). We intended to evaluate the primary outcome irrespective of valve brand manufacturer, vascular access used, deployment technique/mechanism (auto-expandable vs mechanical).…”
Section: Search Strategy Selection Criteria and Data Extractionmentioning
confidence: 99%
“…In 1975, McAlpine, by citing their findings, referred to the feature as "anterior part of the ostial slope" focusing on its prominent angulated aspect. 2 These early observations have been followed by many studies, [3][4][5][6][7][8][9][10][11][12][13][14][15] focusing on the morphological and physiological aspects of the sigmoid septum of living hearts. Specifically, subsequent studies have confirmed the association between the sigmoid septum and systemic hypertension.…”
Section: Introductionmentioning
confidence: 99%
“…5,6,8,14,15 Localized hypertrophy has also been found in patients showing the sigmoid septum. [4][5][6][7][8]12,14,15 Apart from the original definition, this localized hypertrophy has been used as a diagnostic criterion for the sigmoid septum, 5,6,8,11,15,16 and some studies even preferred to use such terms as "basal/localized subaortic/septal hypertrophy" and "discrete upper septal hypertrophy" to describe this feature, 4,5,8,15 instead of the original term "sigmoid septum." Reflecting this conceptual confusion during the establishment of the definition of the sigmoid septum, there was even a study that differentiated this localized hypertrophy from the sigmoid septum, 12 as they considered the sigmoid septum to be a concept without hypertrophy, as suggested by Goor et al 1 In clinical practice, the morphological concept of the sigmoid septum generally seems to involve the resultant septal bulge with or without localized septal hypertrophy.…”
Section: Introductionmentioning
confidence: 99%